ANALISIS WACANA KRITIS: METODE ANALISIS DALAM PERSPEKTIF NORMAN FAIRCLOUGH - Endang Sumarti (Jurnal Bahasa Lingua Scientia, 2010)
The analysis of texts both written and spoken is not explicitly and systematically correlated to the discourse structure. Some critical linguistic contributions and social semiotics have been ignored. According to Van Dijk, a discourse is developed by three dimensions: texts, social cognition and social contexts. Quite similarly, Norman Fairclough’s analysis is conducted based on a main question how can a micro text be related to the macro social contexts.